TEACHING HERITAGE BOOKS TO IMPROVE READING SKILLS AT THE SALAFIYAH HAMIDIYYAH INSTITUTE IN BULUREJO-DIWEK-JOMBANG SCIENTIFIC RESEARCH - Muhamad Yusrur Roziq; Abdul Qadir; Arif Setiabudi (Kampus Akademik Publiser, 2025)
The background to this research is that although most students have followed the learning process, many are still unable to read the yellow book well. This indicates a gap between the methods used and the expected results, especially in mastering the skill of reading yellow books. The research problem is summarized in (1) What are the steps of teaching the book at the “Salafiyyah Hamidiyyah” Institute in Bolorejo-Dewek-Jombang? (2) How to improve reading skills at the “Salafiyyah Hamidiyyah” Institute in Bolorejo-Dewek-Jombang? The objectives of this research are: (1) To know the steps of teaching the book at the “Salafiyyah Hamidiyyah” Institute in Bolorejo-Dewek-Jombang, and (2) To know the improvement of reading skill in the